What drives athlete loyalty? The interplay of service quality and satisfaction in banjarmasin city - Hazri Irsyad Dwinando; Fanlia Prima Jaya; Adam Saputra (Hut Publication Business and Management, 2026)
The quality of service that athlete recevice from a sports development organization plays a substantial role in shaping how satisfied and loyal they remain toward development program in which they participate. This Study sets out to measure the extent to which service quality relates to athlete satisfaction and athlete loyalty, as well as to examine the effect of service quality on athlete loyaty with satisfaction acting as a mediating variable among athlete in Banjarmasin City. A quantitative method was employed, covering a population of 202 athlete who took part in the 2025 South Kalimantan Regional Student Sports Week (Popda), with 100 respondents drawn as the sample through a stratified random sampling technique. Data were gathered through a Likert scale 1-5 with Google Form questionnaire and subsequently processed using the Partial Least Square approach with the assistance of SmartPLS 3 software. The findings reveal a positive and significant link between service quality and both athlete satisfaction and athlete loyalty, and athlete satisfaction is furhter shown to serve as a significant mediator within the pathway through which service quality influences loyalty, The implication is that continuously enhancing service throughout the development process is essential for sustaining both the satisfaction and the loyalty of regional athletes.